Implementation of value engineering in optimizing project's cost for energy infrastructure asset development - Sarmad Dashti Latif (2023)
Value Engineering, one of the proven tool and the best system that should be applied to manage with the competitive environment of the industry. Using the Value Engineering toll does not influence the cost reduction only, but also it is improved that value engineering has a positive impact on the development of varieties of constructions such as both initial and life-cycle costs of the construction projects. This study aimed to verify the strength and the drawback of this application through studying the most recent articles in the same area. Then, the paper reported on the main objectives to optimize cost by analyzing a case study of TNB project in Malaysia and building PMU Project specifically. This was by implement Value Engineering as an effective tool. Findings from this study approved the implementation of Value Engineering has successfully reduced the cost.